Biomechanical analysis of reinstating buccally flared maxillary 2nd molars using 3D printing anchorage supports: a 3D finite element study. Issue 10 (7th September 2021) - Kuang, Yunchun; Wang, Chunjuan; Hu, Bo; Feng, Ge; Wang, Chao; Song, Jinlin
Abstract: The buccally flared maxillary 2nd molar has certain consequences on oral function and health. However, existing methods have some degree of disadvantages, such as invasion, complexity and side effects. The objectives of this study were to design anchorage systems to correct buccally flared maxillary 2nd molars and analyze their biomechanical effects by 3-dimensional (3D) finite element analysis. Finite element (FE) models of the 3D tanspalatal arches (TPAs) and 3D splints with different thicknesses and force points were constructed. The stress distribution on teeth, the hydrostatic pressure on periodontal ligaments and the initial displacement of teeth were analyzed. A total of 18 FE models were constructed and analyzed. The stress concentrated on a single anchorage tooth, and the hydrostatic pressure and initial displacement of the anchorage tooth were greater than those of the malposed 2nd molar in the 3D splint anchorage system. The stress spread on all anchorage teeth and the hydrostatic pressure and initial displacement of the anchorage tooth were less than those of the malposed 2nd molar in the 3D TPA anchorage system. Theoretically, the 3D TPA was better than the 3D splint as an anchorage to correct the buccally flared 2nd molar. A combination of 0.8 mm of thickness and mesial force point provided the optimal conditions for the 3D TPA. Further clinical studies should be conducted to verify the effects of 3D appliances.